University Community Engagement and the Strategic Planning Process - Newton Miller, Laura (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2018)
Objectives – To understand how university libraries are engaging with the university community (students, faculty, campus partners, and administration) when working through the strategic planning process.